Students’ Skills Performing Mathematical Reasoning and Communication through Group Investigation Learning Model - Muhamad Sabirin; Aminah, Siti; Muhniansyah; Muh. Fajaruddin Atsnan (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2021)
The general purpose of learning mathematics formulated by the National Council of Teachers of Mathematics (NCTM) states that students must learn mathematical communication, mathematical reasoning, mathematical problem solving, mathematical connections, and mathematical representation. This study aims to describe and analyze students’ mathematical reasoning and communication skills on linear programming material through the GI type cooperative learning model. This research is quasi-experimental design of the non-equivalent posttest only control group design. The research population was all students of class XI MAN 3 Banjar. The research sample is class XI IIS using cooperative learning model type GI and class XI MIA 1 using conventional learning. Data collection techniques was using observation, documentation, and tests. The results of the study shows that: (1) the mean score of the mathematical reasoning skills and the mathematical communication skills within the students of Grade XI State Madrasah Aliyah 3 Banjar on the learning materials of Linear Program through the GI-Type Cooperative Learning Model is 81.12 and 83.20, respectively belong to the “Very Good” qualification; (2) the mean score of the mathematical reasoning skills and the mathematical communication skills within the students of Grade XI State Madrasah Aliyah 3 Banjar on the learning materials of Linear Program through the Conventional Learning Model is 70.13 and 77.98 respectively belong to the “Very Good” qualification; (3) there have been differences on the mathematical reasoning skills on the learning materials of Linear Program between the students of Grade XI State Madrasah Aliyah 3 Banjar who have been exposed to the GI-Type Cooperative Learning Model and those who have been exposed to the Conventional Learning Model; and (4) there have been differences on the mathematical communication skills on the learning materials of Linear Program between the students of Grade XI State Madrasah Aliyah 3 Banjar who have been exposed to the GI-Type Cooperative Learning Model and those who have been exposed to the Conventional Learning Model.